The Symptoms and prophylaxis of venous thromboembolism in the population of cancer and hospice patients-what is known? - Justyna Składanek; Michał Leśkiewicz; Piotr Daniel; Karina Otręba; Joanna Cieszkowska; Karolina Czupryńska (Journal of Education, Health and Sport, 2024)
In a group of palliative patients, venous thromboembolism (VTE) is a significant cause of death and reduction in quality of life. Current guidelines and scientific research on thromboprophylaxis most often refer to the population of oncology patients, who differ in many aspects from patients receiving palliative care. Thus, doctors working with patients undergoing palliative treatment have to face many problems related to safety and effectiveness of antithrombotic therapy in this type of care.